Comunicação Governamental: em busca de um alicerce teórico para a realidade brasileira - Haswani, Mariângela Furlan (Organicom, 2006)
The article focuses on governmental communication in a conjuncture of a deep crisis of institutional legitimacy. In this scenario, and considering the history of the formation of the Brazilian State as a factor that impairs the necessary changes, it presents the proposals of some Italian authors, which were also conceived in the middle of the crises in that country and can contribute to the creation of a Brazilian state communication model.